1991
DOI: 10.1017/s037689290002172x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Removal-capacity of Four Chosen Aquatic Macrophytes in Tropical Freshwater Ponds

Abstract: The nutrient removal-capacity of four chosen aquatic macrophytes was tested in both natural and laboratory conditions. Laboratory experiments were performed under controlled conditions using ‘microcosm’ methods wherein the plants were grown in three different nutrient concentrations. For field experiments, three ponds were selected that had different levels of plant nutrient concentrations and accordingly were treated as polluted, moderately polluted, and relatively unpolluted, respectively, the object being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Unlike V. spiralis, the presence of L. aequinoctialis was found to have a significant effect only on one water quality variable, namely total phosphorus (Figure 1f). The phosphorus uptake capacity of Lemna has been reported in tropical ponds (Tripathi et al 1991) and being a free-floating plant, water possibly happens to be its sole source of phosphorus. Philipose et al (1970) also observed an association between the free-floating form specially Lemna and phosphorus rich water (0.05 to 3.6 mgl -1 ) in a survey of Indian water bodies including farm ponds.…”
Section: Presence/absence Of Hydrophytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike V. spiralis, the presence of L. aequinoctialis was found to have a significant effect only on one water quality variable, namely total phosphorus (Figure 1f). The phosphorus uptake capacity of Lemna has been reported in tropical ponds (Tripathi et al 1991) and being a free-floating plant, water possibly happens to be its sole source of phosphorus. Philipose et al (1970) also observed an association between the free-floating form specially Lemna and phosphorus rich water (0.05 to 3.6 mgl -1 ) in a survey of Indian water bodies including farm ponds.…”
Section: Presence/absence Of Hydrophytesmentioning
confidence: 99%
“…Due to mild winters in tropical regions, plants grow throughout the year thus, annual data is necessary to understand habitat tolerance and preference limit of individual species. There is a paucity of data on the occurrence of different plant species in relation to the water quality in tropical ponds (Mukhopadhyay & Dewanji 2002) although there are reports of independent studies of aquatic plants (Tripathi et al 1991) as well as of water quality in relation to the growth of phytoplanktons (Bhaskaran et al 1991). This data could also be valuable in respect to botanical conservation (Angélibert et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For the concentrations of total nitrogen values between 50% and 96% of reduction were found, and for phosphorus between 36% and 90%, allowing for the environmental conditions to which E. crassipes is exposed (Debusk & Reddy, 1987;Tripathi et al, 1991;Sharma & Oshodi, 1991;Zakova et al 1994). …”
Section: Concentrations Of Nitrogen and Phosphorus In The Water Of Thmentioning
confidence: 99%
“…Thus, showing the high potential of this species to remove many compounds. The species of the genus Salvinia exhibit a lower efficiency in systems of sewage treatment, when compared to other floating aquatic macrophytes (Reddy & Debusk, 1985;Tripathi et al, 1991). According to ROOM (1986), these plants can offer efficient pollution removal only when carefully managed.…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, il serait possible d'entrevoir la possibilité de cultiver une plante aquatique sur un plan d'eau donné subissant une pollution continue en composés azotés et phosphorés (MARIN, 1993), pour assurer une certaine productivité en biomasse. Dans ce sens, les données présentées dans le tableau 1 mettent en évidence l'importance du choix de la plante aquatique pour optimiser les procédures d'épuration, en concordance avec les potentiels valorisables désirés (AXTELL et al, 2003;FONKOU, 1996;REDDY et DEBUSK, 1987;TRIPATHI et al, 1991). Le choix de la plante à cultiver n'est pas aisé, car il doit satisfaire plusieurs critères (HAUSLER et al, 1994).…”
Section: Introductionunclassified